Complete remission with sunitinib in a poor-risk patient with metastatic renal cell carcinoma. Issue 4 (April 2015) - Massari, Francesco; Ciccarese, Chiara; Bimbatti, Davide; Fantinel, Emanuela; Modena, Alessandra; Simbolo, Michele; Brunelli, Matteo; Artibani, Walter; Martignoni, Guido; Scarpa, Aldo; Tortora, Giampaolo
<x xml:space="preserve">Abstract</x> Sunitinib represents a reasonable therapeutic option for first-line treatment of poor-risk metastatic renal cell carcinoma and the treatment should aim at the delicate balance between managing side effects to improve the toxicity profile and patient compliance to treatment while maintaining anticancer efficacy. Achievement of a complete response, although rare, is possible, even in poor-risk patients. Treatment discontinuation represents a viable alternative for both tumour biology and patients' quality of life. To date, no molecular markers have been identified with prognostic and/or predictive value for guiding therapeutic decisions. Further research should aim at gaining in-depth knowledge of renal cell carcinoma biology for a tailored personalized therapy. We report a case of poor-risk metastatic renal cell carcinoma, with Von Hippel—Lindau loss of function, which achieved and maintained a complete remission after first-line therapy with sunitinib by using a reduced dosage and a modified schedule of treatment.